Building relations in the renewed democracy (Educação e Pesquisa, 2002)
How do we - equals and different - build relations in a democracy in which individuals benefit from rights that protect them from the omnipotence of the apparatuses of cultural conformation? Democracy is here defined as the respect for human and personal rights against the usurpation promoted by those apparatuses. It is the regime of freedom of expression, of freedom of association. It is a space for freedom of consciousness for people, and a space for the rights of the minorities. It is about promoting the construction of the Agent in the tension between an integrative identity and a conflictual identity, pointing out that any recognition of the actor's action relies on its insertion in a social relation. The creation of spaces for debate by the actor will allow him to question his distancing from the conditions for the production of his life. Those spaces for debate remind us of the need, in the middle of a society in transformation, of promoting the domains of adventure, the places of life, and not the places for living, where the Other has its place, and the farthest from the violence that wants to reduce the Other to the same. Through debate, a factor of de-dramatization of everyday life, one deals with the recreation of the social relation having at its center everyone's ability to produce his/her life.